SME mineral processing & extractive metallurgy handbook - Kawatra, S. K.; Young, Courtney, 1962- (Society for Mining, Metallurgy & Exploration (SME), 2019)
"The Mineral Processing & Extractive Metallurgy Handbook is a mining and minerals reference book including information on mineral characterization and analysis, management and reporting, comminution, classification and washing, transport and storage, physical separations, flotation, solid and liquid separation, hydrometallurgy, pyrometallurgy, and processing of selected metals, minerals, and materials"--